(untitled) (AYUSHDHARA, 2021)
Ayurveda is an ancient and most trusted Indian system of medicine commonly used by Indians since time immemorial. Lifestyle diseases/ Metabolic diseases are described as diseases related to the way an individual or group of individuals live, also are referred under Non-Communicable Diseases. Over-crowding and rapid unplanned urbanization; globalization of unhealthy lifestyles is responsible for some of the major reasons for a sedentary life leading to these diseases. It includes arteriosclerosis, heart disease, stroke, obesity and type-2 diabetes, diseases related to smoking, alcohol and drug abuse. The contribution of metabolic risk factors such as high blood pressure, blood sugar, cholesterol and that of improper diet and alcohol use resulting in health loss. Therefore, the occurrence of these disorders has doubled in India over the past quarter of a century therefore it is the need of the hour to manage them diligently. Diet plays a key role to nourish life and balanced diet is very important for maintaining good health. In Ayurveda, wholesome diet is described which plays a very important role specifically rather than in modern medicine which emphasizes only on the components in the diet like proteins, carbohydrates, fats etc. Ayurveda additionally deals with various other aspects like combination of food article, their quantity, method of preparation, their emotional effect, nature of consumer including environmental considerations. Pathya and Apathya Ahara (dietary consideration) is a significant component of almost each and every prescription in Ayurveda therapy. Sometimes, Pathya-Apathya (dietary management) is itself an entire treatment.